Jan Floris de Jongh (1910 - 1988), President of IASSW 1954-1961 - Albert Riga (Social Work & Society, 2007)
Jan Floris de Jongh played an undoubtedly significant role in the development of social work within and beyond The Netherlands. Yet, he and his contributions to the field are barely known, particularly in The Netherlands. His achievements warrant much more attention given that this Dutchman was also one of the most relevant figures in the international social work community. According to data in the Amsterdam Municipal Archives, Jan Floris de Jongh was born on April 7, 1910 in Buitenzorg in the former Dutch East Indies (now Bogor, Indonesia).   The archives state that he was a registered lawyer in Amsterdam in 1933 and moved to The Hague to pursue a career as a civil servant in the Ministry of Economic Affairs in 1934. In the same year, he married Nel ter Weele. During his career at the Ministry (1934-1946) he witnessed considerable changes which influenced his views of society namely, the Great Depression and the German Occupation of The Netherlands in World War II.